Leadership and teamwork competencies development through an outdoor experiential training program - Κουρτεσοπούλου, Άννα (Πανεπιστήμιο Πελοποννήσου, 2015)
There is a great need for professional development in times of a rapid economic growth. Common areas of global competences focus on flexibility and adaptation, leadership skills, teamwork and strategic thinking. For the conduction of this study, the following research questions were used: (1) Are there any immediate effect on teamwork as a result of the training? (2) Are there any immediate effect on leadership competencies as a result of the training? (3) Are there any differences between the professional and student group in post teamwork and leadership scores? (4) Are there any differences among participants of each group in post teamwork and leadership scores based on demographic variables such as age and gender? A mixed research method using qualitative and quantitative data was used, following a retrospective pretest-posttest design. A non-probability convenience sample of purpose was used including two predefined groups (professionals, n = 51) and (undergraduate students, n = 30). The intervention was a 2-day outdoor experiential training program including a series of small group activities, followed by short debriefing sessions. The Multifactor Leadership Questionnaire-MLQ (Bass & Avolio, 1997) was used to measure three types of leadership styles (transformational, transactional, passiveavoidant) and three outcomes of leadership styles (extra effort, perceived effectiveness, satisfaction with leadership). Perceptions of team effectiveness were measured by the Team Development Indicator (TDI-short version, Bronson, 1991). The following major findings were identified: For both groups the intervention was effective as post scores in TDI were significantly higher than pre-test scores. Overall teamwork appeared in higher level after training, indicating a moderate change in professionals and a large change in students. Transformational and transactional leadership styles were displayed frequently in post training at the professional group, indicating a moderate change, where passive/avoidant behaviors decreased significantly. Similarly, transformational leadership and the decrease of passive/avoidant leadership revealed a large change in post training at the student group. Significant difference found in students who perceived more frequent teamwork behaviors than professionals in post training. Female reported greater levels compared to male respondents in transformational leadership, and were prompt to develop those behaviors that generate satisfaction in followers. The category of below 22 years old exhibited less frequent passive behaviors and displayed the highest score in total teamwork. Also, the categories of 23-29 and above 35 years old made less extra effort. Professionals in a responsible position, with a working experience between four and eight years acquired lower level of teamwork behaviors. Also those who had changed more than three different working environments affiliated with higher level of extra effort behaviors.
Ανάπτυξη ηγετικών δεξιοτήτων και ομαδικής εργασίας δια μέσου προγράμματος υπαίθριας βιωματικής εκπαίδευσης
Keywords: Leadership; Teamwork; Competencies; Outdoor experiential training; Development; Ηγετικές δεξιότητες; Ομαδική εργασία; Υπαίθρια βιωματική εκπαίδευση; Ανάπτυξη